Early Gastric Cancer with Purely Enteroblastic Differentiation and No Conventional Adenocarcinoma Component. (28th August 2018) - Yamada, Rin; Horiguchi, Shin-ichiro; Onishi, Tomoko; Motoi, Toru; Hishima, Tsunekazu
Abstract : Gastric carcinoma with enteroblastic differentiation (GCED) is a rare variant of gastric carcinoma, and a part of GCED produces alpha-fetoprotein. GCED is characterized by cells with clear cytoplasm and a tubulopapillary and solid growth pattern resembling those in the primitive gut. GCED is typically overlaid by a conventional adenocarcinoma (CA) component, implying that CA in the mucosa differentiates into GCED during tumor invasion and proliferation. We present the case of a 73-year-old woman with a 10-mm superficial elevated lesion and a slight central depression at the anterior wall of the lower gastric body. Endoscopic submucosal dissection revealed tumor cells having clear cytoplasm and severely atypical nuclei characteristic of GCED. The growth pattern was predominantly solid and trabecular but included submucosal layer invasion and limited tubular growth. Atrophic pyloric mucosa without intestinal metaplasia surrounded the tumor. Immunohistochemically, the tumor cells were positive for AFP, GPC3, and SALL4. The present patient showed a purely enteroblastic differentiation without a CA component despite the presence of early cancer, indicating that few cases of GCED may arise de novo in the gastric mucosa. GCED is more aggressive compared with CA; therefore, pathologists should be aware that GCED without CA can appear in biopsy specimens of early cancer while making an accurate diagnosis.